Enhancing Resilience in Mathematics Education : Evaluating Chinese Targeted Intervention Strategies - Xia, Wang; Amalia, Madihie (CANA, 2025)
Introduction: This study developed and validated a mathematics-specific resilience intervention program tailored for Chinese university students, integrating Sidek's resilience framework with Delphi method-based expert consensus.